(untitled) (Global Journals of Research in Engineering, 2025)
To ensure successful steps to a low carbon economy and total electrification commitments to deep decarbonization in North America require regional power system integration The most efficient solution for regional power integration enabling competitive electricity wholesale is proven by Regional Transmission Organizations RTO The RTO concept and practices ensure high efficiency and reliability of regional electricity markets and power transmission system operations To improve power integration of regional and inter-regional electricity trade using an RTO approach the last frontiers for organized wholesale markets in North America should be identified addressed and resolved One of important frontiers for competitive regional electricity wholesale in North America is presented by Atlantic Canada An Atlantic RTO ARTO here manifests a key upgrade and an important component of the Canadian Electricity System addressing its generation mix transmission structure and regulatory framework and advancing inter-regional East-West and North-South power integration The ARTO would enable best-in-class regulations that strengthen existing policies for the electricity sector and should be seen as a compelling high priority in leveraging the Clean Grid 2035 target in Canada A collaborative framework for the ARTO decision-making can be used to identify and financially support inter-regional electricity transmission projects and outline their governance cost allocation and funding components The ARTO is positioned as a critically important regional integration advancement in Canada s deep decarbonization pathways Strong connection between Deep Decarbonization and Deep Regional Inter-regional Electricity Market Integration concepts and practices reinforces the role of the Atlantic RTO in realizing Canada s 2030 Emissions Reduction Plan It ensures the benefits of electricity market integration in Atlantic Canada such as increased diversity of generation mix improved system reliability increased supply security and demand diversity Prompt deployment and operation of the Atlantic RTO would make the region more competitive nationally and internationally Timely coordination and cooperation of the government private academic and civil electricity sub-sectors on multiple levels in the Atlantic region is suggested so as to achieve the ARTO deployment within the 2025-2035 timeframe As a part of the cooperative action the ARTO development and deployment would greatly benefit from the existing electricity system operator skillset of the industry in New Brunswick and Nova Scotia The civil electricity sub-sector should be promptly engaged with deep participation of Canada s First Nations so as to leverage personal organizational and societal developments in the region